1984
DOI: 10.1051/rnd:19840707
|View full text |Cite
|
Sign up to set email alerts
|

ATP measurement in sheep rumen digesta using dimethyl sulfoxide as an extraction reagent

Abstract: Summary. Dimethyl sulfoxide (DMSO) Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…However, there was high interindividual variation and this was not consistent with the changes in SCFA with sampling time. Large interindividual variations in ATP concentration of rumen digesta have also been reported (Erfle et al 1981 ; Komisarczuk et al 1984). Thus, in contrast to previous results obtained in rats or pigs (Bach Knudsen et al 1984, the validity of this indicator for the young rabbit remains to be confirmed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, there was high interindividual variation and this was not consistent with the changes in SCFA with sampling time. Large interindividual variations in ATP concentration of rumen digesta have also been reported (Erfle et al 1981 ; Komisarczuk et al 1984). Thus, in contrast to previous results obtained in rats or pigs (Bach Knudsen et al 1984, the validity of this indicator for the young rabbit remains to be confirmed.…”
Section: Discussionmentioning
confidence: 86%
“…SCFA were measured by gas chromatography (CP9000, Chrompack, Middelburg, The Netherlands) by the method of Jouany (1982) adapted to a semi-capillary column and NH, concentrations were measured by the technique of Weatherburn (1967) with an autoanalyser (Technicon, Domont, France). The concentration of ATP in caecal digesta was estimated by the luciferinluciferase (EC 1.13.12.7) method (McElroy, 1947;Komisarczuk et al 1984) (ATP dosing kit, BioOrbit, Turku, Finland). Calculations Apparent faecal digestibility was calculated from individual and daily total collections of faeces performed during six consecutive days.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Glycogen content of the cell suspension was assayed using a-amylo 1 4 , 1 4 glucosidase according to Roehring and Allred (31). ATP content of cells isolated from 2-d-old suckling pigs and incubated for 30 min with 2 mM glucose was measured by the luciferin-luciferase system after extraction with dimethyl sulfoxide (32). Galactokinase (EC 2.7.1.6) activity was determined in homogenates of enterocytes (n = 3) isolated from 0-d-old, 2-d-old suckling, 12-d-old, and postweaning animals, according to the method of Ballard (33).…”
Section: Animalsmentioning
confidence: 99%
“…Samples were taken after a new equilibration period of 4 days, judged sufficient from the volatile fatty acid (VFA) production which stabilized. ATP concentrations were measured in the liquid phase of the vessels four times a day (just before and 2, 4 and 6 h after the feed bag was changed) and in the washed solid residues, as described by Komisarczuk, Durand and Hannequart (1984). One ml of liquid or 1 g of solid was treated with 9 ml of dimethylsulfoxide for ATP extraction and ATP was determined by bioluminescence.…”
mentioning
confidence: 99%